A comparative evaluation of skeletal, dental, and soft tissue changes with skeletal anchored and conventional facemask protraction therapy - Tulika Tripathi; Priyank Rai; Navneet Singh; Shilpa Kalra (Wolters Kluwer Medknow Publications, 2016)
Objective: To cephalometrically evaluate and compare the skeletal, dentoalveolar, and soft tissue changes after maxillary protraction with skeletally anchored and conventional facemask. Methods: The data for the study were collected from the pre- and post-treatment records of patients of maxillary retrusion treated with skeletally anchored and conventional facemask therapy. Twenty subjects were included in the study and were categorized into two groups, namely skeletal anchored maxillary protraction (SAMP) group with the mean age of 10.10 ± 1.1 years and conventional facemask maxillary protraction (CFMP) group with the mean age of 9.90 ± 1.1 years. Pre and post-treatment lateral cephalograms were assessed. Results: The data were analyzed by Mann-Whitney test and Wilcoxon signed-rank test. The mean duration of treatment in SAMP group and CFMP group was 5.8 months and 10 months, respectively. The mean forward displacement of the maxilla (vertical point A) was 3.40 ± 1.07 mm in SAMP group and 2.80 ± 0.79 mm in CFMP group. The mandible showed downward and backward rotation in both the groups with more rotation in CFMP group. A significant increase in maxillary incisor inclination was seen in CFMP group as compared to SAMP group. A significant decrease was found in mandibular incisor inclination in both the treatment groups. The soft tissue changes corresponded to underlying skeletal tissue. C onclusions: SAMP is proven to be a better treatment modality as compared to CFMP for achieving true skeletal changes and minimal dental changes in cases with developing skeletal Class III with maxillary retrusion.